Effects of standard and low doses of estradiol on markers of endometrial receptivity in frozen-thawed embryo transfer cycles: Double-blind, randomized clinical trial - Nichamon Parkpinyo; Isarin Thanaboonyawat; Japarath Prechapanich; Pitak Laokirkkiat; Roungsin Choavaratana; Suchanan Hanamornroongruang; Somsin Petyim (PLoS ONE, 2025)
Background Endometrial receptivity biomarkers, specifically the regulatory proteins HOXA-10 and HOXA-11 as well as the integrin αvβ3, play vital roles in implantation during the window of implantation. This Double-blinded, randomized clinical trial compares the effects of two initial doses of oral estrogen regimens on endometrial receptivity markers during the window of implantation in endometrial preparation for frozen-thawed embryo transfer. Methods and findings The study includes infertile patients who underwent in vitro fertilization and planned frozen-thawed embryo transfer at the infertility clinic between June 2018 and March 2019. Fifty patients were randomized to a low-dose (4 mg/day) or standard-dose (6 mg/day) estradiol group for artificial endometrial preparation. On the first visit (day 12 of the cycle), measurements of mean endometrial thickness and estradiol and progesterone levels were taken. Following this visit, patients received 600 mg daily of micronized progesterone for 7 days. On the second visit (day 19 of the cycle), hormonal levels were reassessed, and an endometrial biopsy was performed for immunohistochemical analysis. The primary outcome was the expression level of HOXA-10. Secondary outcomes included the expression levels of HOXA-11 and integrin αvβ3, mean endometrial thickness, as well as serum estradiol and progesterone levels measured at various phases of the endometrial cycle. The mean age of the participants was 36 years. The standard-dose group exhibited significantly greater intensity scores for the expression of the regulatory proteins HOXA-10 and HOXA-11 and the integrin αVβ3 than did the low-dose group (75.84 ± 11.25 vs 61.53 ± 11.05, 107.08 ± 19.42 vs 87.62 ± 9.40, and 90.25 ± 10.42 vs 76.32 ± 12.98, respectively; P < 0.001). The groups had no significant differences in mean serum estradiol level, progesterone level, or endometrial thickness during the artificial cycle at the first or second visit. Conclusions Optimal artificial endometrial preparation for embryo transfer in a frozen-thawed embryo transfer cycle is crucial for maximizing implantation outcomes. This study suggests that the administration of a fixed standard dose of 6 mg of estradiol for artificial endometrial preparation should be considered.